Improved methods, properties, applications and prospects of microbial induced carbonate precipitation (MICP) treated soil: A review - Xuanshuo Zhang; Hongyu Wang; Ya Wang; Jinghui Wang; Jing Cao; Gang Zhang (Biogeotechnics)
Soil improvement is one of the most important issues in geotechnical engineering practice. The wide application of traditional improvement techniques (cement/chemical materials) are limited due to damage ecological environment and intensify carbon emissions. However, the use of microbially induced calcium carbonate precipitation (MICP) to obtain bio-cement is a novel technique with the potential to induce soil stability, providing a low-carbon, environment-friendly, and sustainable integrated solution for some geotechnical engineering problems in the environment. This paper presents a comprehensive review of the latest progress in soil improvement based on the MICP strategy. It systematically summarizes and overviews the mineralization mechanism, influencing factors, improved methods, engineering characteristics, and current field application status of the MICP. Additionally, it also explores the limitations and correspondingly proposes prospective applications via the MICP approach for soil improvement. This review indicates that the utilization of different environmental calcium-based wastes in MICP and combination of materials and MICP are conducive to meeting engineering and market demand. Furthermore, we recommend and encourage global collaborative study and practice with a view to commercializing MICP technique in the future. The current review purports to provide insights for engineers and interdisciplinary researchers, and guidance for future engineering applications.